Effects of short-term administration of tolvaptan after open heart surgery. (1st October 2016) - Matsuyama, Katsuhiko; Koizumi, Nobusato; Nishibe, Toshiya; Iwasaki, Tomoaki; Iwahasi, Toru; Toguchi, Kayo; Takahashi, Satoshi; Iwahori, Akinari; Maruno, Keita; Ogino, Hitoshi
Abstract: Background: Postoperative fluid overload following cardiac surgery is associated with increased morbidity and mortality. Unlike loop diuretics, tolvaptan (TLV) promotes aquaretic effect. Relatively little has been documented regarding the efficacy of TLV after cardiac surgery. The aim of the study was to investigate the effectiveness and safety of tolvaptan for the management of immediately postoperative fluid retention following cardiac surgery. Methods: Between January to May 2014, patients undergoing cardiac surgery were randomly assigned to control or TLV group immediately after cardiac surgery. In control group, patients received 20 mg of furosemide and 25 mg of spironolactone as conventional diuretics. In the TLV group, 7.5 mg of TLV was administered in combination with conventional diuretics. Results: TLV use was associated with increased urine output from postoperative day 1 to 3.Body weight reduction in the TLV group was significantly greater than the control group from postoperative day 2 to 4, and serum creatinine levels decreased to below preoperative values in the TLV group. Conclusions: The combination of tolvaptan with conventional diuretics increases urine output without renal dysfunction and can be effective for postoperative fluid management and appropriate body weight reduction.